A Fully-Integrated CMOS Dual-Band RF Energy Harvesting Front-End Employing Adaptive Frequency Selection - Wen Xun Lian; Harikrishnan Ramiah; Gabriel Chong; Kishore Kumar Pakkirisami Churchill; Nai Shyan Lai; Saad Mekhilef; Yong Chen; Pui-In Mak; Rui P. Martins (IEEE Access, 2023)
This paper proposes a fully-integrated dual-band CMOS RF energy harvesting (RFEH) front-end with an adaptive frequency selector that can select between two harvesting frequencies of 1.9 GHz and 2.4 GHz. The RFEH front end includes two pairs of on-chip LC networks and rectifiers that convert the harvested RF power into a usable DC voltage. An internal control logic circuit, powered by an auxiliary path, selects the input harvesting frequency band with a higher power output to the load. The proposed dual-band adaptive frequency selection RFEH system achieves a peak PCE of 40% and 32% at 1.9 GHz and 2.4 GHz, respectively.